2008
DOI: 10.4137/cmo.s524
|View full text |Cite
|
Sign up to set email alerts
|

Review: Mitochondrial Defects in Breast Cancer

Abstract: Mitochondria play important roles in cellular energy metabolism, free radical generation, and apoptosis. Mitochondrial DNA has been proposed to be involved in carcinogenesis because of its high susceptibility to mutations and limited repair mechanisms in comparison to nuclear DNA. Breast cancer is the most frequent cancer type among women in the world and, although exhaustive research has been done on nuclear DNA changes, several studies describe a variety of mitochondrial DNA alterations present in breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Although haplogrouping is primarily used for identifying relationships among individuals and populations, some haplogroups possess sequence variants that also contribute to cancer susceptibility ( 26 28 ). Moreover, some somatic mutations may represent haplogroup conversion ( 29 ), complicating interpretability of mtDNA data.…”
Section: The Mitochondrial Genome’s Mutational Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Although haplogrouping is primarily used for identifying relationships among individuals and populations, some haplogroups possess sequence variants that also contribute to cancer susceptibility ( 26 28 ). Moreover, some somatic mutations may represent haplogroup conversion ( 29 ), complicating interpretability of mtDNA data.…”
Section: The Mitochondrial Genome’s Mutational Landscapementioning
confidence: 99%
“…Although variants of this type (especially from slippage associated with mononucleotide repeats) are often discussed with substitutions in cancer literature, they are presented here with other structural variants given the nature of the genetic variation. High levels of nuclear MSI throughout the nuclear genome have been associated with tumorigenesis in some types of cancer ( 29 , 80 ). Frequency of this hypermutator phenotype within and across cancer types, however, is variable, and nuclear MSI is not associated with mitochondrial MSI ( 81 ) or mtDNA mutations in general ( 82 ).…”
Section: The Mitochondrial Genome’s Mutational Landscapementioning
confidence: 99%
“…mtDNA has been studied as a potential biomarker in assessing the risk of developing breast cancer in certain populations (21,22). The mitochondrial D-loop region has been shown to be a hotspot of variations associated with breast cancer (23). In addition, mutations located between positions 303 and 315 are frequently observed in cancer (24).…”
Section: Introductionmentioning
confidence: 99%
“…Other frequently reported mtDNA mutations associated with breast cancer is at the NADH dehydrogenase subunits 1,2,4,5 ATP synthase F0 subunit 8, cytochrome c oxidase subunit III. Mutations in 12s and 16s rRNA have also been reported in breast cancer patients [132,143]. Another study identified novel tRNA mutations in two breast cancer cell lines [144].…”
Section: Mitochondrial Defects In Breast Cancermentioning
confidence: 98%
“…However, the mitochondrial heterogeneity among breast cancer patients has remained a neglected area of breast cancer research. Defects in mitochondrial functions, mitochondrial genome defects including reduced copy numbers, germline or somatic mtDNA mutations and Microsatellite Instability (MSI) have been reported in a high percentage of breast cancer patients [128][129][130][131][132][133][134]. Clinical reports from various cohorts and The Cancer Genome Atlas (TCGA) show a significant percentage of hormone receptor (Estrogen and Progesterone receptor) and Herceptin (HER2) Triple Negative Breast Tumors (TNBC) are highly aggressive and have poor prognostic outcomes.…”
Section: Mitochondrial Defects In Breast Cancermentioning
confidence: 99%